Embodied Subjects of Victimization: The Year in Korea - Park, Heui-Yung (Biography (Honolulu), 2020)
Commonly referred to in Korea as the "ttangk'ong hoehang sakön" [nut-fly-back incident], it resulted from a temper tantrum by Cho Hyön-a (Heather Cho), vice president of Korean Air and the oldest daughter of its CEO, Cho Yang-ho. Because macadamia nuts were served to her in a bag instead of on a plate, she became furious with the flight attendant, accusing her of not following the in-flight service manual correctly. Pak's forced removal from the flight and Chang's suicide resulted from kapchil culture in South Korea, which stems from the unequal relationship between the privileged and the "other" Borrowed from a contractual term, kap indicates an individual or group who has the upper hand over the disadvantaged ül in society, and chil is a derogatory word for bad conduct. By presenting their own stories or those of others wronged in Korean society, Pak and Yun disclose how the disadvantaged such as themselves have been abused by the privileged, and ask their readers to judge their cases-examples of Leigh Gilmore's notion of autobiographical representation as an "alternative jurisdiction" (715), where unrestrained by legal protocols, individuals can speak for themselves and the vulnerable. [...]I will discuss the vulnerabilities of life writing itself, as shown by the controversies over Yun's testimony and their ramifications. Since the publication of her book, Yun has been accused of being a false witness, of taking advantage of Chang's case for monetary gain, and of trying to increase her own popularity.